Using natural materials as corrosion inhibitors for carbon-steel on phosphoric acid medium - Mohammed, Rawaa Abbas; AL-mammar, Dunya E. (Iraqi Journal of Science, 2019)
The inhibitive action of pomegranate peel as a plant source the corrosion of carbon-steel in phosphoric acid solutions was studied using the weight-loss method. Organic compounds present in natural materials are successfully used to reduce the rate of corrosion because they are cheap, renewable and effective. The results showed that the inhibition potency was enhanced with increasing increasing the amount of the inhibitor and the immersion time but it decreased with the increase of the concentration of the acid solution. The results also revealed a gradual increase in the corrosion rate with the increase of temperature, while the corrosion protection efficiency and surface coverage decreased.